Moderate correlation between systemic IL‐6 responses and CRP with trough concentrations of voriconazole. (19th June 2018) - Vreugdenhil, Bas; van der Velden, Walter J. F. M.; Feuth, Ton; Kox, Matthijs; Pickkers, Peter; van de Veerdonk, Frank L.; Blijlevens, Nicole M. A.; Brüggemann, Roger J. M.
Abstract : Aims: Voriconazole (VCZ) exhibits wide intrapatient pharmacokinetic variability, which is disadvantageous because of its narrow therapeutic range. A considerable part of this variation remains unexplainable, despite extensive knowledge of this drug. It is hypothesized that inflammation has an impact on VCZ pharmacokinetics. In the present study, we investigated the correlation between VCZ trough concentrations and various cytokines. Methods: A prospective single‐centre analysis was performed in adult haematology patients receiving VCZ for possible, probable or proven invasive fungal disease. A linear mixed model was built to explore the contribution of each of the seven pro‐ and anti‐inflammatory cytokines to VCZ trough levels. The Akaike information criterion (AIC) was used to determine the model that fitted the best. Results: Twenty‐two patients, with a total of 143 combined samples of VCZ trough levels and cytokines, were included. A significant correlation ( P < 0.005) was found between VCZ trough concentrations and interleukin (IL) 6, IL‐8 and C‐reactive protein (CRP). IL‐6 showed the lowest AIC, although differences with the other mediators were marginal. Conclusion: VCZ trough concentrations correlate with IL‐6, IL‐8 and CRP levels but only moderately explain the variability in VCZ pharmacokinetics. Future prospective studies should be undertaken to confirm these findings, and incorporate the data obtained into pharmacokinetic models, to refine the predictive behaviour.